2017
DOI: 10.1089/chi.2017.0042
|View full text |Cite
|
Sign up to set email alerts
|

A Social Media Peer Group for Mothers To Prevent Obesity from Infancy: The Grow2Gether Randomized Trial

Abstract: A social media peer-group intervention was engaging and significantly impacted certain feeding behaviors in families with infants at high risk of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 53 publications
1
99
0
1
Order By: Relevance
“…After duplicate removal, and title and abstract screening, 230 references were selected for full‐text review. One hundred and eighty eligible studies were identified, describing 39 trials, comprising 46 interventions . Five trials had more than one eligible intervention arm .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicate removal, and title and abstract screening, 230 references were selected for full‐text review. One hundred and eighty eligible studies were identified, describing 39 trials, comprising 46 interventions . Five trials had more than one eligible intervention arm .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two trials had positive impacts on behavioural outcome measures only (Table S5). Behavioural targets of these interventions were breastfeeding,; infant feeding: bottle feeding (bottle weaning); infant feeding: introduction to solids and child feeding; breastfeeding and complementary feeding; infant and child feeding/eating and breastfeeding; sleep; maternal eating habits; multiple behaviours: infant feeding (including breastfeeding and introduction to solids), sleep, parenting; infant feeding, diet, physical activity, and television viewing; infant feeding, infant physical activity, sedentary behaviour; infant feeding, infant physical activity, sedentary behaviour, sleep; infant/child feeding and physical activity …”
Section: Resultsmentioning
confidence: 99%
“…Though prior work has described low-income mothers’ self-reported internet and social media use [ 28 ] and the social support received from such groups [ 6 , 7 , 10 – 12 ], this is the first study that examines the content and accuracy of information shared in a social media parenting group of low-income mothers. Prior work has shown that mothers considered the Grow2Gether Facebook group a supportive environment and mothers actively engaged in the group, posting an average of 30 times per week [ 20 , 21 ]. Mothers were eager to both ask and answer infant health questions in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The forty-four mothers randomized to the Grow2Gether control group of text message appointment reminders were not included in the present study because they did not participate in the Facebook groups. Details of the Grow2Gether intervention have been previously described [ 20 , 21 ]. Participating mothers were recruited to Grow2Gether at their obstetrics appointments between the 20th and 34th week of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation